Emotional correlates of unirhinal odour identification. Issue 1 (2nd January 2016) - Wilkinson, David; Moreno, Sergio; Ang, Chee Siang; Deravi, Farzin; Sharma, Dinkar; Sakel, Mohamed
ABSTRACT: It seems self-evident that smell profoundly shapes emotion, but less clear is the nature of this interaction. Here, we sought to determine whether the ability to identify odours co-varies with self-reported feelings of empathy and emotional expression recognition, as predicted if the two capacities draw on common resource. Thirty-six neurotypical volunteers were administered the Alberta Smell Test, the Interpersonal Reactivity Index and an emotional expression recognition task. Statistical analyses indicated that feelings of emotional empathy positively correlated with odour discrimination in right nostril, while the recognition of happy and fearful facial expressions positively correlated with odour discrimination in left nostril. These results uncover new links between olfactory discrimination and emotion which, given the ipsilateral configuration of the olfactory projections, point towards intra- rather than inter-hemispheric interaction. The results also provide novel support for the proposed lateralization of emotional empathy and the recognition of facial expression, and give reason to further explore the diagnostic sensitivity of smell tests because reduced sensitivity to others' emotions can mark the onset of certain neurological diseases.